2005
DOI: 10.1111/j.1572-0241.2005.41822.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Serum Alanine Aminotransferase Activity and Age: An Inverted U Curve Pattern

Abstract: Our data suggest a significant association between age and serum ALT activity. This association is not a simple linear correlation, but rather an inverted-U-like relation. Thus, when interpreting the laboratory results of a subject suspected of liver disease, age should probably be taken into account. Larger-scale studies are needed to better characterize this issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
58
4
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(74 citation statements)
references
References 7 publications
6
58
4
6
Order By: Relevance
“…Similar co relation between age and ALT activity was reported by previous report, where an inverted U like relation of ALT and age was revealed (Elinav et al, 2005). Some studies have reported significant association of ALT activity with gender, in the current study a significant difference in ALT activity with gender was found only among Non-Diabetics at p=0.005.…”
Section: Resultssupporting
confidence: 90%
“…Similar co relation between age and ALT activity was reported by previous report, where an inverted U like relation of ALT and age was revealed (Elinav et al, 2005). Some studies have reported significant association of ALT activity with gender, in the current study a significant difference in ALT activity with gender was found only among Non-Diabetics at p=0.005.…”
Section: Resultssupporting
confidence: 90%
“…However, no subanalysis was performed on the nondiabetic group for CVD-related death only; therefore, these results are not as pure as the other two studies. It appears that any proposed linear relationship between ALT and incident CVD is debatable, as others have recently shown that ALT may in fact exhibit a U-shaped association with total mortality 24,25 and unpublished data from our group (Ford et al) suggests that ALT's associations with CVD events may be similarly shaped with increased risk also apparent at low ALT concentrations. Thus, current evidence goes against a linear association of ALT with CVD events.…”
mentioning
confidence: 74%
“…In addition, since the average ALT level for six of seven patients was Ͻ40 U/liter but Ͼ20 U/liter, these results illustrate the occurrence of host immune selection even with a slight increase in average ALT level. Although the cutoff of 20 U/liter may seem arbitrary, the ALT levels of hepatitis-free populations of different age groups have never exceeded this level (13,41). To this extent, an ALT level of 20 U/liter may represent the action of host immunity against HBV.…”
Section: Discussionmentioning
confidence: 99%